Trait Emotional Intelligence in Surgeons - Petrides, K. V.; Perazzo, Matheus F.; Pérez-Díaz, Pablo A.; Jeffrey, Steve; Richardson, Helen C.; Sevdalis, Nick; Ahmad, Noweed (Frontiers in Psychology, 2022)
Trait emotional intelligence (trait EI or trait emotional self-efficacy) concerns people’s perceptions of their emotional functioning. Two studies investigated this construct in surgeons and comparison occupations. We hypothesized that trait EI profiles would differ both within surgical specialties as well as between them and other professions. Study 1 (N = 122) compared the trait EI profiles of four different surgical specialties (General, Orthopedic, Head and Neck, and Miscellaneous surgical specialties). There were no significant differences amongst these specialties or between consultant surgeons and trainees in these specialties. Accordingly, the surgical data were combined into a single target sample (N = 462) that was compared against samples of engineers, executives and senior managers, lawyers, junior military managers, nurses, and salespeople. Surgeons scored significantly higher on global trait EI than junior military managers, but lower than executives and senior managers, salespeople, and nurses. There were no significant differences vis-à-vis engineers or lawyers. A MANOVA confirmed a similar pattern of differences in the four trait EI factors (Wellbeing, Self-control, Sociability, and Emotionality). Global trait EI scores correlated strongly with single-question measures of job satisfaction (r = 0.47) and job performance (r = 0.46) in the surgical sample. These findings suggest that interventions to optimize the trait EI profiles of surgeons can be helpful in relation to job satisfaction, job performance, and overall psychological wellbeing.